The Williams Act after RICO: Has the Balance Tipped in Favor of Incumbent Mangement - August, Andrew A. (1983)
In 1968, Congress passed the Williams Act primarily to regulate two favored methods of corporate takeovers-substantial stock acquisitions and tender offers. By the early 1980s, attorneys representing target corporations had discovered a potent supplement to the Williams Act--the Racketeer Influenced and Corrupt Organizations Act (RICO), which was enacted in 1970. Corporate attorneys have interpreted RICO's provisions to give tender offer targets an express right to sue under RICO for certain violations of the Williams Act. This Article explores the problems raised by the policy conflict that emerges from this use of Williams Act violations when stating a cause of action under RICO. The Article first describes the Williams Act and RICO, examining the pertinent statutory provisions, their legislative history, and the Supreme Court's interpretation of this legislative history. The central purposes of each act are identified. The Article then examines the two reported cases in which target corporations have used alleged violations of the Williams Act to state a claim under RICO, and argues that the judicial approval of such RICO suits places the goals of the two statutes in irreconcilable conflict. The result is that in a corporate takeover battle, RICO tips the balance Congress sought to establish in the Williams Act in favor of incumbent management. The Article concludes that because of this irreconcilable conflict, the two statutes cannot be harmonized when involved in the same litigation, and that the Williams Act, as the more precise and detailed of the two statutes, should apply to the exclusion of RICO